Brown-colored malignant pleural fluid with high bilirubin levels: a case series - Nai-Chien Huan; Larry Ellee Nyanti; Lee, Xin Ying; Hema Yamini Ramarmuty; Eng, Daniel Theng Sheng; Kunji Kannan Sivaraman Kannan; Lee, Gary Yun Chor (John Wiley & Sons Ltd, 2024)
Brown-colored pleural effusion is rare and may result from high bilirubin levels such as bilothorax (often described as a pleural fluid-to-serum bilirubin ratio of > 1.0). We describe four patients with malignant pleural effusion that appeared macroscopically brown with a pleural fluid-to-serum bilirubin ratio between 3.7 and 16.2. All had metastatic adenocarcinomas; three were from lung and one from gastric origin. None demonstrated clear pleurobiliary fistulas on investigations. Postulates for the development of brown effusion include heme oxygenase 1 overexpression in malignant cells situated in the pleura, intrapleural hemolysis, passive movement of bile through microscopic diaphragmatic pores, and drainage of biliary fluid into the pleural lymphatics.